Who's Buying by Race and Hispanic Origin. (Amityville, New York : New Strategist Press, LLC, 2015)
The tenth edition of Who's Buying by Race and Hispanic Origin is based on unpublished data collected by the Bureau of Labor Statistics' 2013 Consumer Expenditure Survey, data you can't get online. It presents detailed product-by-product household spending statistics for Asians, Blacks, Hispanics, and non-Hispanic Whites organized into ten chapters: apparel, entertainment, financial products and services, food and alcoholic beverages, gifts for people in other households, health care, household operations, shelter, transportation, and a chapter that looks at personal care, reading, education, and tobacco.
Household spending trends, 2000 to 2013 -- Spending overview, 2013 -- Spending on apparel, 2013 -- Spending on entertainment, 2013 -- Spending on financial products and services, 2013 -- Spending on food and alcoholic beverages, 2013 -- Spending on gifts for people in other households, 2013 -- Spending on health care (out-of-pocket expenses), 2013 -- Spending on housing : household operations, 2013 -- Spending on housing : shelter and utilities, 2013 -- Spending on personal care, reading, education, and tobacco, 2013 -- Spending on transportation, 2013.
Description based upon print version of record.
Keywords: African American consumers -- Statistics; Asian American consumers -- United States -- Statistics; Consumers -- United States -- Statistics; Consumers' preferences -- United States -- Statistics; Ethnicity -- Economic aspects -- United States -- Periodicals; Hispanic American consumers -- United States -- Statistics; Ethnicity -- Economic aspects -- United States -- Statistics; Consumers -- United States -- Statistics; African American consumers -- United States -- Statistics; Hispanic American consumers -- United States -- Statistics; Electronic books; African American consumers; Consumers; Ethnicity -- Economic aspects; Hispanic American consumers; United States; Statistics